SEKOLAH UNGGULAN SEBAGAI KEBIJAKAN STRATEGIS: EVALUASI KONSEP, IMPLEMENTASI DAN DAMPAKNYA - Maudinah, Nur Hikmah; Musgamy, Awaliah (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the policy of flagship schools as a strategy to improve educational quality by examining its conceptual foundations, key components of implementation, and the impacts and challenges it poses for educational equity. Using a library research method, this study reviews various literature, regulations, and empirical findings related to the concept of flagship schools, school-based management, teacher professionalism, curriculum innovation, and the provision of adequate facilities. The findings indicate that flagship schools are supported by strong policy frameworks designed to enhance the quality of learning by ensuring a conducive learning environment, competent educators, and enriched curricula. The implementation of this policy has contributed to improved student achievement and strengthened quality culture within schools. However, the study also identifies several consequences, including potential disparities in access, discriminatory student selection, and unequal distribution of resources across schools. Additional challenges include limited funding, shortages of qualified human resources, resistance to change, administrative bureaucracy, and mismatches between national policies and local contexts. These findings highlight the need for flagship school policies to be designed in a more inclusive, adaptive, and equitable manner so that they not only produce high academic achievement but also support the broader goal of equitable educational quality nationwide.